Co-Electrodeposition of Metallic Precursors for the Fabrication of CZTSe Thin Films Solar Cells on Flexible Mo Foil. Issue 6 (1st January 2017) - Khalil, M. I.; Bernasconi, R.; Pedrazzetti, L.; Lucotti, A.; Donne, A. Le; Binetti, S.; Magagnin, L.
Abstract : Earth abundant Cu2 ZnSnSe4 (CZTSe) thin films solar cells were fabricated on flexible molybdenum (Mo) foil substrate through an electrochemical approach. After co-electroplating from single electrolyte, Cu-Zn-Sn (CZT) precursor was selenized in quartz tube furnace at 550°C for 15 minutes in Ar atmosphere with the presence of elemental selenium in order to form CZTSe compound. Before selenization, CZT precursor was soft-annealed at 310°C for 150 minutes in Ar atmosphere in order to improve intermixing of the elements and to reduce roughness. The formation of Kesterite CZTSe on selenized film was confirmed by X-ray diffraction (XRD) and Raman spectroscopy. SEM imaging and EDS line profile on the cross-section of CZTSe layer showed the well-formed CZTSe along depth of the film also. Opto-electrical characteristics of the film by photoluminescence spectroscopy confirmed the suitability of the absorber layer to make solar cell. A flexible solar cell with Al/Al-ZnO/i-ZnO/CdS/CZTSe/Mo-foil configuration, which showed 0.1% power conversion efficiency at first attempt, has been fabricated, in which buffer layer CdS has been deposited through chemical bath deposition and transparent conducting oxides (i-ZnO, Al-ZnO) have been deposited by DC pulsed sputtering.